Elevated body mass index as a causal risk factor for symptomatic gallstone disease: A Mendelian randomization study - Stender, Stefan; Nordestgaard, Børge G.; Tybjærg‐Hansen, Anne (Hepatology (Baltimore, Md.), 2013)
Elevated body mass index (BMI) is associated with an increased risk of gallstone disease. Whether this reflects a causal association is unknown. Using a Mendelian randomization approach, we studied 77,679 individuals from the general population. Of these, 4,106 developed symptomatic gallstone disease during up to 34 years of follow‐up. Subjects were genotyped for three common variants known to associate with BMI: FTO(rs9939609); MC4R(rs17782313); and TMEM18(rs6548238). The number of BMI‐increasing alleles was calculated for each participant. In observational analyses, mean baseline BMI was 55% (11.6 kg/m2) increased in individuals in the fifth quintile versus the first quintile, similar in women and men. The corresponding multifactorially adjusted hazard ratio (HR) for symptomatic gallstone disease was 2.84 (95% confidence interval [CI]: 2.32‐3.46) overall, 3.36 (95% CI: 2.62‐4.31) in women, and 1.51 (95% CI: 1.09‐2.11) in men (P trend: 0.001 to <0.001; P interaction: BMI*sex on risk = 0.01). In genetic analyses, carrying 6 versus 0‐1 BMI‐increasing alleles was associated with a 5.2% (1.3 kg/m2) increase in BMI overall and with increases of 4.3% in women and 6.1% in men (all P trend: <0.001). Corresponding HRs for symptomatic gallstone disease were 1.43 (95% CI: 0.99‐2.05) overall, 1.54 (95% CI: 1.00‐2.35) in women, and 1.19 (95% CI: 0.60‐2.38) in men (P trend = 0.007, 0.02, and 0.26, respectively; P interaction allele score*sex on risk = 0.49). The estimated causal odds ratio (OR) for symptomatic gallstone disease, by instrumental variable analysis for a 1 kg/m2 increase in genetically determined BMI, was 1.17 (95% CI: 0.99‐1.37) overall and 1.20 (95% CI: 1.00‐1.44) and 1.02 (95% CI: 0.90‐1.16) in women and men, respectively. Corresponding observational HRs were 1.07 (95% CI: 1.06‐1.08), 1.08 (95% CI: 1.07‐1.10), and 1.04 (95% CI: 1.02‐1.07), respectively. Conclusion: These results are compatible with a causal association between elevated BMI and increased risk of symptomatic gallstone disease, which is most pronounced in women. (Hepatology 2013; 58:2133–2141)